Effects of e-aid cognitive behavioural therapy for insomnia (eCBTI) to prevent the transition from episodic insomnia to persistent insomnia: study protocol for a randomised controlled trial - Yang, Yuan (BMJ Open, 2019)
INTRODUCTION: Previous evidence suggested that online self-guided sleep intervention is efficacious in improving treatment outcomes in patients with persistent insomnia. However, research on online sleep interventions targeting episodic insomnia has been scarce. This study aims to evaluate the effectiveness of brief e-aid cognitive behavioural therapy for insomnia (eCBTI) in preventing transition from episodic insomnia to persistent insomnia. METHODS AND ANALYSIS: This is a pragmatic two-arm multicentre, randomised controlled trial comparing eCBTI with treatment as usual (TAU) in outpatients. Two hundred patients with episodic insomnia (as defined by DSM-5) will be recruited. Patients will be randomly assigned to receive 1 week eCBTI via a Smartphone application, or to receive TAU. Treatment effects will be assessed at 1 week and 3 months after intervention. The primary outcome of the study, whether the eCBTI program is sufficient in preventing transition from short-term to persistent insomnia, is measured by the Insomnia Severity Index. Secondary outcome measurements include the Dysfunctional Beliefs and Attitudes about Sleep Scale, Ford Insomnia Response to Stress Test, Sleep Hygiene and Practices Scale, Pre-sleep Arousal Scale and Epworth Sleepiness Scale. Additionally, the Hospital Anxiety and Depression Scale and the Short-Form 12-Item Health Survey will be used for measurement of mood symptoms and quality of life. ETHICS AND DISSEMINATION: Ethical approval for the study has been obtained from the Ethics Committee of Southern Medical University (reference number: NFEC-2017–131). The results of the investigation will be published in scientific papers. The data from the investigation will be made available online if necessary. TRIAL REGISTRATION: NCT03302455 (clinicaltrials.gov). Date of registration: October 5, 2017.